Influence of different solvents on the structural, optical and morphological properties of CdS nanoparticles - Oliveira, J. F. A.; Milao, T. M.; Araujo, V. D.; Moreira, M. L. [UNESP]; Longo, Elson [UNESP]; Bernardi, M. I. B. (Elsevier B.V. Sa, 2011)
CdS is one of the most important II-VI semiconductors, with applications in solar cells, optoelectronics and electronic devices. CdS nanoparticles were synthesized via microwave-assisted solvothermal technique. Structural and morphological characterization revealed the presence of crystalline structures presenting single phase with different morphologies such as "nanoflowers" and nanoplates depending on the solvent used. Optical characterization was made by diffuse reflectance and photoluminescence spectroscopy, revealing the influence of the different solvents on the optical properties due to structural defects generated during synthesis. It is proposed that these defects are related to sulfur vacancies, with higher concentration of defects for the sample synthesized in ethylene glycol in comparison with the one synthesized in ethylene diamine. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: CdS; Nanoparticles; Microwave-assisted Solvothermal; Optical properties